Strategi Pembelajaran Untuk Meningkatkan Kemampuan Baca Tulis Al-Quran Pada Anak-Anak Di Desa Padang Pelawi, Seluma - Agung Herlambang; Alisa Susanti; Fhatur Heksa Setiawan; Lisa Mawarni; Nor Khoirola Rega Duita; Nur Hidayanti; Rahma Mifthahuljanna; Rizky Riyandi Rahmadan; Yepi Junita; Zahra Ayuri; Eka Sri Wahyuni (MENYALA: Jurnal Pengabdian Masyarakat, 2024)
This research aims to increase interest and ability to read and write the Koran in children in Padang Pelawi Village, Seluma. Through a descriptive qualitative approach, this research identified the main problems, namely the lack of teaching staff and children’s interest. The learning strategies implemented include talaqqi, playing, story and singing (BCM) methods, as well as iqra and tartil. The research results showed that the implementation of this strategy was successful in increasing children’s interest and ability to read and write the Koran. Apart from that, a fun approach like BCM also makes the learning process more interesting and effective.